2021
DOI: 10.3390/su13020958
|View full text |Cite
|
Sign up to set email alerts
|

Usage and User Characteristics—Insights from MOIA, Europe’s Largest Ridepooling Service

Abstract: New, i.e., shared and digitized, mobility services have been entering urban mobility markets around the globe. Among these new offerings is ridepooling, a mobility solution that bundles requests from passengers with similar routes in real-time and matches them with a vehicle. Ridepooling is quite novel in Germany and knowledge about users, changes in travel behavior, and impacts on the urban traffic system is scarce. To address this gap, we conducted an online survey among users and non-users of MOIA, a German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
15
1
1
Order By: Relevance
“…This is surprising, as other studies (e.g., Chen et al [66]) have found that this construct is relevant in the transportation context. As can be seen from the descriptive statistics (Appendix A.1), the respondents tend to use ridepooling for leisure activities, consistent with the study of Kostorz et al (32), rather than for regular transportation (e.g., commuting). This led to the assumption that ridepooling is a service for short and occasional rides, whereas ridesharing is used for longer trips between cities.…”
Section: Discussion Recommendations and Implications For Academicssupporting
confidence: 83%
See 2 more Smart Citations
“…This is surprising, as other studies (e.g., Chen et al [66]) have found that this construct is relevant in the transportation context. As can be seen from the descriptive statistics (Appendix A.1), the respondents tend to use ridepooling for leisure activities, consistent with the study of Kostorz et al (32), rather than for regular transportation (e.g., commuting). This led to the assumption that ridepooling is a service for short and occasional rides, whereas ridesharing is used for longer trips between cities.…”
Section: Discussion Recommendations and Implications For Academicssupporting
confidence: 83%
“…The study of Kostorz et al (32) reveals a more diverse view on ridepooling users, finding that the 20 to 39 age group represented 49% of the user population for ridepooling services. Compared with this, non-users of ridepooling seem to be in the age groups of 50 and older (32). Based on the sample in the present study, no claims can be made for recommendations on these older target groups, since they are underrepresented in this study.…”
Section: Discussion Recommendations and Implications For Academicscontrasting
confidence: 57%
See 1 more Smart Citation
“…We have implemented regular bicycles; but station-based as well as free-floating e-bikes, scooters, Segways, mopeds, and other similar modalities are gaining traction in urban environments. Ride-sharing concepts (e.g., MOIA in Hamburg) are becoming increasingly established alternatives to public transport [4]. Connected and Autonomous Vehicles (CAV) are entering the mainstream, promising to reshape transport and become a cornerstone of smart mobility [7,43].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the typical set of stops (home → work/school → home) has become increasingly broken up into longer chains with multiple subroutes [3]. Secondly, new mobility solutions such as shared or on-demand vehicles have grown in popularity (e.g., [4]). These developments lead to the concept of Mobility-as-a-Service [5,6].…”
Section: Introductionmentioning
confidence: 99%